Use of Extra-judicial Technical Surveillance in Criminal Decision-making: European Limitations and National Challenges - Andrei Zarafiu (Societas et Iurisprudentia)
At the European level, the general rule for the gathering of evidence and the use of investigative methods involving the restriction of fundamental rights and freedoms is that these activities should only be carried out by bodies with judicial powers, only by means of judicial instruments and only in the framework of judicial proceedings. This judicial exclusivity is respected even when pro-active criminal investigations, as it ensures a mechanism of checks and balances on measures consisting in violations of individual rights. The case law of the European Court of Human Rights in Strasbourg has consistently stated that even a severe threat to national security, such as acts of terrorism, or other risks of a global nature are not to be relied upon in order to override this form of protection and control. The present study aims to address the particular situation of technical surveillance carried out through specific intelligence gathering activities that restrict the exercise of fundamental rights or freedoms. Beyond the essential issue of the admissibility of the use of information obtained by officers (bodies) specializing in national security activities as evidence in criminal proceedings, the analysis aims to identify controversies and offer solutions on other issues of interest: the ability of non-judicial bodies to become involved in the conduct of criminal investigations, the effectiveness of the mechanisms for controlling these intrusive methods, the conformity with the European law of national regulations allowing such participation, the way in which information gathered by extrajudicial bodies can influence the criminal decision-making process. The analysis will be carried out from both the European and the national perspective, taking into account the particularities of the Romanian judicial system.